The Phenomenon of Leadership – Complexity of Dimesions - Rafał KOZŁOWSKI (Communications of International Proceedings, 2021)
The field of strategic management has become increasingly concerned with leaders and their effects on strategy formulation, firm performance, and Child’s (1972) notion that leader’s decisions and choices impact firm performance. The idea has been further developed in the work of Hambrick and Mason (1984), and it has since been widely cited and expanded (Canella & Monroe, 1997; Finkelstein & Hambrick, 1996). According to Mischel (1977), strategic decisions due to their complexity and ambiguity may be interpreted by different leaders most diversely and can vary widely (Finkelstein & Hambrick, 1996; House & Aditya, 1997). This paper was prompted by a need to investigate leadership processual approach. The phenomenon of leadership is considered as a dynamic, situation-based social process that is contingent upon culture and context.
Keywords: Leadership; Strategic Management